Concept for development of economically alloyed ausferritic (bainitic) ductile cast irons - A. I. Pokrovsky (Литьë и металлургия)
The distribution of the castings production in the world, whose total output is more than 112 million tons, is considered. A steady trend to the replacement of rolled alloy steel, which is used for critical engineering products, by Austempered Ductile Iron (ADI) is outlined. The latter is ductile cast iron with globular graphite, which is austempered (isothermally quenched) to produce ausferritic (bainitic) structure. The dynamics of prices for main alloying elements in ADI (molybdenum, nickel and copper, whose total amount in the alloy reaches 5 %) is considered and their steady growth is outlined.The research goal is to develop a concept of economical alloying of ADI (the total content of Mo, Ni and Cu should not exceed 2 %) retaining sufficient hardenability and substantially decreasing the cost price. The goal is attained by decreasing the content of the most expensive alloying element, molybdenum, to a minimal level along with the use of microalloying and applying one of the methods of hot plastic deformation to the casting.The reduced content of the main ‘triad’ of alloying elements is compensated by microadditives of strontium or barium, vanadium, boron, niobium and the addition of misch metal. Several groups of economically alloyed cast irons are proposed: (1) low‑nickel and low‑molybdenum with increased content of copper (up to 1.8 %) and the addition of vanadium, (2) molybdenum‑free with microadditive of boron, (3) molybdenum‑free with microadditives of niobium and boron, and (4) molybdenum‑free minimally alloyed with nickel and copper.It is shown that plastic deformation, along with giving the product the required shape, affects the kinetics of structural‑phase transformations. and acts similarly to alloying with Mo and Ni, shifting the TTT‑curve to the right. Therefore, the ausferritic structure can be obtained at a lower cooling rate.The mechanical properties with such alloying and the use of plastic deformation are the following: ultimate tensile strength 1100–1500 MPa and elongation to failure 2–4 % for lower bainite; ultimate tensile strength 800–1100 MPa and elongation to failure is 4–7 % for upper bainite.